2011
DOI: 10.1007/s12010-011-9191-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Transaldolase Gene Tal from Saccharomyces cerevisiae in Fusarium oxysporum for Enhanced Bioethanol Production

Abstract: The filamentous fungus Fusarium oxysporum is known for its ability to ferment xylose-producing ethanol. However, efficiency of xylose utilization and ethanol yield was low. In this study, the transaldolase gene from Saccharomyces cerevisiae has been successfully expressed in F. oxysporum by an Agrobacterium tumefaciens-mediated transformation method. The enzymatic activity of the recombinant fungus (cs28pCAM-Sctal4) was 0.195 times higher than that of the wild-type strain (cs28). The recombinant strain also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Also, the recombinant strain had even lower biomass yields than the wild type. Although the transaldolase activity was only 0.195 times higher than the wild type, this different effect, compared to our results, can be attributed to either the different experimental layout or the increased enzyme production in our work [25]. In a very similar study, the same group showed that final biomass in a F. oxysporum strain overexpressing a transaldolase from P. stipitis was lower than that of a wild type strain during growth on xylose [26].…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…Also, the recombinant strain had even lower biomass yields than the wild type. Although the transaldolase activity was only 0.195 times higher than the wild type, this different effect, compared to our results, can be attributed to either the different experimental layout or the increased enzyme production in our work [25]. In a very similar study, the same group showed that final biomass in a F. oxysporum strain overexpressing a transaldolase from P. stipitis was lower than that of a wild type strain during growth on xylose [26].…”
Section: Resultscontrasting
confidence: 75%
“…g substrate −1 are normally found for aerobic growth of filamentous fungi [32], but lower yields are also reported for some filamentous fungi due to extensive byproduct formation [33]. Fan et al [25] reported lower biomass yields for wild type strain F. oxysporum cs28 and the recombinant strain overexpressing the S. cerevisiae sctal. Also, the recombinant strain had even lower biomass yields than the wild type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in two very similar studies, Fan et al showed that heterologous overexpression of a transaldolase resulted in lower biomass yields than when using the parental strain. 10,11 On the other hand, our homologous overexpression of both phosphoglucomutase and transaldolase resulted in an increase in the maximum specific growth rate and a biomass yield similar to that of the parental strain, when using glucose as the sole carbon source. With xylose, the same strain had much higher biomass yields and a slightly higher maximum specific growth rate.…”
mentioning
confidence: 86%
“…Also, the accumulation of sedoheptulose-7-P when the microorganism was grown in glucose-xylose mixtures under oxygen-limiting conditions, and of erythrose-4-P during xylose consumption (Panagiotou et al, 2005b ), indicated a second bottleneck in the F. oxysporum metabolism. Fan et al reported the effect on F. oxysporum of the overexpression of transaldolase genes from Pichia stipitis and S. cerevisiae , which increased both xylose consumption and ethanol production when either glucose or xylose was used as carbon source (Fan et al, 2011a , b ) in shake flask batch cultures.…”
Section: Introductionmentioning
confidence: 99%